2008
DOI: 10.1158/0008-5472.can-07-5818
|View full text |Cite
|
Sign up to set email alerts
|

γ-Irradiation–Induced DNA Damage Checkpoint Activation Involves Feedback Regulation between Extracellular Signal-Regulated Kinase 1/2 and BRCA1

Abstract: Previous studies from our laboratory have shown that the activation of G2-M checkpoint after exposure of MCF-7 breast cancer cells to γ-irradiation (IR) is dependent on the activation of extracellular signal-regulated kinase 1/2 (ERK1/2) signaling. Studies presented in this report indicate that IR exposure of MCF-7 cells is associated with a marked increase in expression of breast cancer 1 (BRCA1) tumor suppressor, an effect that requires ERK1/2 activation and involves posttranscriptional control mechanisms. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…In this study, the activation of MAPK by stress-inducing agents promoted an increased level of phosphorylated H2AX, a marker of DNA damage caused by double-strand breaks [54], as demonstrated previously in other cellular systems [19][20][21][22]55,56]. actions as sensors of DNA strand break sites [57].…”
Section: Accepted Manuscriptsupporting
confidence: 81%
“…In this study, the activation of MAPK by stress-inducing agents promoted an increased level of phosphorylated H2AX, a marker of DNA damage caused by double-strand breaks [54], as demonstrated previously in other cellular systems [19][20][21][22]55,56]. actions as sensors of DNA strand break sites [57].…”
Section: Accepted Manuscriptsupporting
confidence: 81%
“…Studies have found that Akt is hyperactivated in many human cancers, as it promotes proliferation and cancer cell survival in response to DNA-damaging agents (Fraser et al, 2011). In addition, the extracellular signal-regulated kinase 1/2 (ERK1/2) is also involved in ATM/ATR-mediated G2/M checkpoint activation (Yan et al, 2007(Yan et al, , 2008. It was found that 160 mM mangiferin dramatically inhibited phospho-Akt and phospho-ERK1/2 as well as total Akt protein in a time-dependent manner; total ERK1/2 protein level was slightly reduced as well after treatment at all time points ( Figure 4K and M).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of other stresses, such as hydroxyurea and ionizing radiation, ERK activation was required for S phase and G 2 /M checkpoint arrest, respectively (48,49). Moreover, Yan et al reported that ionizing radiation-induced ERK1/2 activation required a direct interaction with BRCA1 for G 2 /M cell cycle checkpoint arrest (50). Thus, the evidence suggests that ERK activation by DNA damage may preferentially be involved in cell cycle arrest before cell death.…”
Section: Discussionmentioning
confidence: 99%